Dilema BDSM Bondage And Discipline, Dominance And Submission, Sadism And Mashochism Pada Kaum Penikmat Seksual - Rhena Lastia Putri (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Humans have a basic desire to be accepted, appreciated and wanted by others, in short humans wants to love and be loved by the others. The desire to have intimacy is considered as the basic human desire and can explain the behavior of individuals in relationship (Baumeister & Leary, 1995). Intimacy sometimes influenced by emotional and sexual relationship conditioned by one or both parties. One of the variation and the dynamic of sex that became popular was BDSM. BDSM is an acronym of B which means Bondage, D which means Discipline and also Domination, S which means Submission and also Sadism, and M which means Masochism. BDSM is a sexual practice that has the character of: power exchange where there are inequalities in degree of relationship, suppression, physical restraint and exploration around the pain. The aim of this study was to find the intimacy of the BDSM perpetrators in the IBS community and to see if intimacy in relationships can arise in couples who practice BDSM in their relationships. This study uses descriptive study, and the sample in this study using snowball sampling technique. It is known that there is a picture of intimacy of relationship owned by BDSM partner and partner in IBS community that is high of Knowledge, high of Caring, High of Interdependence, High Mutualitu, High of Trust and High of Commitmen`